Coevolution between transposable elements and recombination - Kent, Tyler V.; Uzunović, Jasmina; Wright, Stephen I. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2017)
One of the most striking patterns of genome structure is the tight, typically negative, association between transposable elements (TEs) and meiotic recombination rates. While this is a highly recurring feature of eukaryotic genomes, the mechanisms driving correlations between TEs and recombination remain poorly understood, and distinguishing cause versus effect is challenging. Here, we review the evidence for a relation between TEs and recombination, and discuss the underlying evolutionary forces. Evidence to date suggests that overall TE densities correlate negatively with recombination, but the strength of this correlation varies across element types, and the pattern can be reversed. Results suggest that heterogeneity in the strength of selection against ectopic recombination and gene disruption can drive TE accumulation in regions of low recombination, but there is also strong evidence that the regulation of TEs can influence local recombination rates. We hypothesize that TE insertion polymorphism may be important in driving within-species variation in recombination rates in surrounding genomic regions. Furthermore, the interaction between TEs and recombination may create positive feedback, whereby TE accumulation in non-recombining regions contributes to the spread of recombination suppression. Further investigation of the coevolution between recombination and TEs has important implications for our understanding of the evolution of recombination rates and genome structure. This article is part of the themed issue ‘Evolutionary causes and consequences of recombination rate variation in sexual organisms’.